Carbonaceous adsorbents from polymers-rubber and plastic wastes for adsorption of methylene blue - Cesar Troca-Torrado; Maria Alexandre-Franco; Carmen Fernandez-Gonzalez; Manuel Alfaro-Dominguez; Vicente Gomez-Serrano (eXPRESS Polymer Letters)
The development of carbonaceous adsorbent (CAs) from rubber of used tires (TR), poly(ethylene terephthalate) plastic bottles (PET) and an industrial PP (plastic)-EPDM (rubber) blend (VR) to be used in water discoloration treatment is studied. Not only the three starting materials separately but also mixtures of two- and three-components at the mass ratios of 50/50 and 75/12.5/12.5 for all of them were used. The CAs were first prepared by heat-treatment of materials at 900°C for 2 h in N2 and at 850°C for 2 h in steam and then characterized by X-ray diffraction (XRD), scanning electron microscopy (SEM), adsorption of N2 at –196°C, mercury porosimetry, FT-IR spectroscopy and measurement of pH of the point of zero charge (pHpzc), and finally tested as adsorbents of methylene blue (MB) in aqueous solution. The yield of the process of preparation of the CAs is significantly higher with TR and quite similar to PET and VR. It noticeably increases or decreases with material mixtures, presumably because of the interaction of VR with TR and PET during such a process. By using such mixtures, larger developments in surface area and porosity are achieved. SBET is 675 m2·g–1 for the sample prepared from the 50/50 mixture of PET and VR (M3), whereas for the products of the separated activation of PET and VR in steam it is 248 and 100 m2·g–1. pHpzc ranges between 5.8 and 11.1. The beneficial effect also concerns the adsorption process of MB. The pseudo-secondorder kinetic constant is 2.69·103 g·mol·h–1 and the Langmuir adsorption capacity is 0.85·103 g·mol·h–1 for M3.